Mapping the Function of Whole‐Brain Projection at the Single Neuron Level. Issue 33 (13th October 2022) - Zhou, Wei; Ke, Shanshan; Li, Wenwei; Yuan, Jing; Li, Xiangning; Jin, Rui; Jia, Xueyan; Jiang, Tao; Dai, Zimin; He, Guannan; Fang, Zhiwei; Shi, Liang; et al.
Abstract: Axonal projection conveys neural information. The divergent and diverse projections of individual neurons imply the complexity of information flow. It is necessary to investigate the relationship between the projection and functional information at the single neuron level for understanding the rules of neural circuit assembly, but a gap remains due to a lack of methods to map the function to whole‐brain projection. Here an approach is developed to bridge two‐photon calcium imaging in vivo with high‐resolution whole‐brain imaging based on sparse labeling with the genetically encoded calcium indicator GCaMP6. Reliable whole‐brain projections are captured by the high‐definition fluorescent micro‐optical sectioning tomography (HD‐fMOST). A cross‐modality cell matching is performed and the functional annotation of whole‐brain projection at the single‐neuron level (FAWPS) is obtained. Applying it to the layer 2/3 (L2/3) neurons in mouse visual cortex, the relationship is investigated between functional preferences and axonal projection features. The functional preference of projection motifs and the correlation between axonal length in MOs and neuronal orientation selectivity, suggest that projection motif‐defined neurons form a functionally specific information flow, and the projection strength in specific targets relates to the information clarity. This pipeline provides a new way to understand the principle of neuronal information transmission. Abstract : An approach is established to couple the functional activities with the whole‐brain projection of the same neuron by GCaMP6 sparse labeling and a cross‐modality cell matching. It extends the understanding of structure–function correlations through obtaining functionally relevant projection motifs or projection strengths at the single neuron level.